ANALYSIS OF DEBT AND DIVIDEND POLICIES ON FIRM VALUE: A QUANTITATIVE APPROACH IN INDONESIA SHARIA STOCK INDEX - Khairi, Himmatul; Nurani, Khadijah; Deswita, Santi (Journal of Applied Accounting and Taxation, 2025)
The primary goal of the firm is to optimize the value of the firm through the use of financial management functions in order to maximize the wealth of the shareholders. Managing the firm's financial structure through debt and dividend policies is one of them. The purpose of this study is to gather empirical data regarding how debt policy and dividend distribution policy affect business value. The Hypothesis Test is a quantitative research approach used in this study. This study uses data analysis techniques and is cross-sectional and time series (panel data: JII 30 years 2018-2023). Regression Analysis of Panel Data. The research hypotheses were assessed using multiple linear regression analysis, and a sample of eleven companies was obtained using purposive sampling. The findings indicate that between 2018 and 2023, debt and dividend policies significantly affect the value of companies listed in the Jakarta Islamic Index. However, only debt policy exhibits a significant impact on firm value when taking into account individual factors among the listed enterprises from 2018 to 2023